INCREASING KNOWLEDGE OF MIDWIFERY STUDENTS ABOUT FLOOD DISASTERS USING THE JIGSAW LEARNING METHOD - Oktarina, Mika; Eliagita, Choralina; Absari, Nuril; Rahmawati, Ida; Utami, Yustri (Nurse and Health: Jurnal Keperawatan, 2024)
Background: Not having had direct experience in dealing with disasters means that students are not ready to be prepared, so disaster education using a jigsaw learning method is needed. Objectives: This research aims to study the effect of the jigsaw learning model on knowledge of flood disasters in level 3 students in the STIKES TMS undergraduate midwifery study program. Methods: The research design used pre-experimental with one group pretest and post test design. The population of this study were all third year undergraduate midwifery students at STIKES TMS totaling 30 (total sampling) using the Wilcoxon test. Results: The knowledge of third level midwifery students at STIKES TMS before the jigsaw method was known to be less than 6 people, 15 people were sufficient and 9 people were good. The knowledge of third level midwifery students of STIKES TMS after the jigsaw method was found to be 3 people lacking, 5 people sufficient and 22 people good Conclusion: The p value = 0.000 means that there is an influence of the jigsaw learning method on knowledge of flood disasters in third year undergraduate midwifery study programs at STIKES TMS Bengkulu